Changing Industrial Relations in Europe - Beaumont, P. B. (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "Changing Industrial Relations in Europe," edited by A. Ferner and R. Hyman.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Changes; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Diffusion of Human Resource Management Innovations - Beaumont, P. B. (Relations Industrielles / Industrial Relations, 1985)
This paper uses a sample of some 300 plants in Britain to examine the extent and nature of inter-organisational diffusion of human resource management innovations.

Statutory Recognition Provisions in Britain, 1976-1980 - Beaumont, P. B. (Relations Industrielles / Industrial Relations, 1983)
This paper assesses the extent to which the union movement in Great Britain was able to realise in practice the potential advantages of the statutory recognition provisions.

Third Party Conciliation and Trade Union Recognition: Some British Evidence - Beaumont, P. B. (Relations Industrielles / Industrial Relations, 1982)
The author uses information obtainedfrom the unpublished conciliation records of the ACAS régional office in Scotland to look at some of the potential influences on the likelihood of a trade union successfully obtaining récognition under these provisions. Three sets of influence are applied using correlation analysis.

Non-Union American Plants in Britain : Their Employment Practices - Beaumont, P. B.; Townley, B. (Relations Industrielles / Industrial Relations, 1985)
This paper examines, through an analysis of survey evidence, whether U.S. non-union plants in Britain are significantly more likely to have certain work practices currently associated with non-union establishments in the United States.

High Technology Industries and Non-Union Establishments in Britain - Beaumont, P. B.; Harris, R. I. D. (Relations Industrielles / Industrial Relations, 1988)
This paper seeks to remedy some existing research deficiencies in Britain where discussions of the high technology non-union relationship have overwhelmingly consisted of small partial studies of the electronics industry.